2022
DOI: 10.31557/apjcp.2022.23.7.2291
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Psychological Wellbeing of Breast Cancer Survivors in the Kingdom of Saudi Arabia

Abstract: Breast cancer treatment could include different therapies like partial or total mastectomy, radiotherapy, and chemotherapy with or without systemic hormonal therapy, depending on stage and estrogen receptor status

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
2
13
1
Order By: Relevance
“…Our results con rmed that Saudi women with breast cancer demonstrated poor HRQOL status with minimum average values of 48.61 and 50.14 for role physical and physical function, respectively, and maximum average values of 56.61 and 55.41 for social function and general health, respectively. As compared to our ndings, studies from Saudi Arabia reported lower to moderate HRQOL scores among Saudi women with breast cancer [20][21][22][23][24]. Similarly, our ndings are in line with previous studies from Bahrain [31], the Eastern Mediterranean region [17], and Asia [4].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results con rmed that Saudi women with breast cancer demonstrated poor HRQOL status with minimum average values of 48.61 and 50.14 for role physical and physical function, respectively, and maximum average values of 56.61 and 55.41 for social function and general health, respectively. As compared to our ndings, studies from Saudi Arabia reported lower to moderate HRQOL scores among Saudi women with breast cancer [20][21][22][23][24]. Similarly, our ndings are in line with previous studies from Bahrain [31], the Eastern Mediterranean region [17], and Asia [4].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the results re ect signi cant variations and heterogeneities in HRQOL among BC survivors living in different countries. While few published studies have been conducted in Saudi Arabia to identify factors predicting HRQOL of breast cancer patients [20][21][22][23][24]. These studies seem to differ substantially in their conclusions with large variances in HRQOL scores from low to high [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety proved to be just as prevalent, as 19% of cancer patients had clinical and 22.6% had subclinical levels of anxiety ( 8 ). A study conducted in Saudi Arabia in 2022 to assess QoL and the psychological wellbeing of breast cancer survivors reported that 57% of the patients had moderate to severe depression and 44% had moderate to severe anxiety, yet only 6.8% of these patients reported receiving psychosocial support ( 12 ). The treatment of cancer can be equally distressing, as it can cause an array of side-effects, including hair loss, pain, and nausea and vomiting, all which impact patients' levels of functioning negatively and cause further deterioration in the mental and physical QoL ( 6 , 10 , 13 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it improves fatigue, pain, and loss of appetite among cancer patients ( 21 , 22 ). Studies conducted in Saudi Arabia have identified various clinical, treatment, and sociodemographic factors that could influence cancer patients' QoL ( 12 , 23 28 ). Factors such as employment status, educational level, and tumor location were associated with major reductions in all QoL domains ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation